Parent-identified strengths of autistic youth. (January 2021) - Warren, Nick; Eatchel, Bridges; Kirby, Anne V; Diener, Marissa; Wright, Cheryl; D'Astous, Valerie
There is a need for strengths-based intervention approaches for autistic youth during the transition to adulthood. In the current study, we explored parent perspectives about youth strengths during adolescence. We combined data from three studies which included semi-structured interviews about parents' perspectives on preparing for adulthood with autistic youth. Total participants included 39 parents of 41 autistic youth (ages 12–19 years, 88% male). Parents of autistic youth described many strengths of their children in the context of conversations about the transition to adulthood. Thematic analysis revealed three subthemes under the broad theme of parental perceptions of strengths: diverse strengths and skills, strengths counterbalanced by challenges, and strengths with supports. Diverse strengths and skills were further categorized using content analysis and included intelligence, creativity, physical abilities, and self-care skills, which notably include some areas often perceived as weaknesses for autistic people. The findings demonstrate that parents are an important source of information about youth strengths during transition planning processes. Understanding the types of strengths that parents observe in their autistic sons and daughters can help inform the development of strengths-based interventions capable of supporting the transition to adulthood. Lay abstract: Autism is a condition frequently characterized by social and communication challenges. Because most research focuses on understanding and reducing challenges, less is known about the strengths of autistic individuals. This is especially true of those who are transitioning into adulthood. We designed this research study to provide information about how parents perceive the strengths of their autistic adolescent children prior to the transition. We reviewed 39 parent interviews from previous research about how they prepare their autistic sons and daughters for adulthood. Without prompting, parents identified many strengths of their autistic children. Diverse strengths and skills they identified included intelligence, creativity, physical abilities, and self-care skills. These strengths are interesting, as they cover traits that are often thought of as areas of difficulty for autistic youth. However, parents also talked about strengths alongside challenges, and how specific supports would be needed to help their sons and daughters fully realize their strengths. These findings are important, as they help us know more about the strengths of autistic youth and how strengths can be supported when preparing for adulthood. Our findings also help reveal strengths that are particularly apparent during the transition to adulthood.